PENERAPAN EVALUASI SUMATIF BERBASIS KOMPETENSI PADA PEMBELAJARAN PAI: DAMPAK TERHADAP PRESTASI BELAJAR DI SDN BEJI TIMUR 1 - Muhammad Faiz Abrar; Mahmudin Sudin (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2025)
This study aims to describe the implementation of competency-based summative evaluation in Islamic Religious Education (PAI) learning at SDN Beji Timur 1 and analyze its impact on student achievement. This study used descriptive qualitative methods through interviews, observations, and document studies to obtain data on the implementation process of summative evaluation and student learning outcomes. The results showed that the implementation of competency-based summative evaluation began to cover cognitive, affective, and psychomotor aspects through assessment forms such as written tests, projects, and religious practices. This implementation had a positive impact on increasing student motivation and learning achievement because it provided space to demonstrate real abilities, not only relying on memorization. However, challenges faced include limited teacher time, uneven understanding of non-cognitive assessment, and parental perceptions that still emphasize numerical scores. This study concluded that competency-based summative evaluation is effective in improving learning achievement comprehensively, and teacher training and intensive communication with parents are needed to optimize implementation.